2007
DOI: 10.20996/1819-6446-2007-3-5-24-30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beta-Blocker Metoprolol on Quality of Life in Elderly Patients With Chronic Heart Failure

Abstract: Влияние бета-адреноблокатора метопролола на качество жизни пациентов старческого возраста с хронической сердечной недостаточностью И.В. Вологдина Кафедра терапии и клинической фармакологии, Санкт-Петербургская медицинская академия последипломного образования Цель. Оценить влияние ретардированной формы кардиоселективного β-адреноблокатора метопролола тартрата на качество жизни пациентов старческого возраста с хронической сердечной недостаточностью (ХСН), осложнившей течение ишемической болезни сердца (ИБС). Мат… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Thus, β-blockers are one of the mainstays of treatment for CHF because of their ability to reverse the neurohumoral effects of the sympathetic nervous system 13 , with ensuring symptomatic benefits by lowering heart rate (HR) and contractility, consequently lowering the mortality of CHF 2,14 . The same has been demonstrated in terms of improving survival 15–17 and quality of life (QoL) of CHF patients, indicating their importance in CHF management 1821 . On the contrary, administration of β -blockers increases the risk of depression 22 , a key factor for deteriorating QoL and increased mortality risk among CHF patients 23 .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, β-blockers are one of the mainstays of treatment for CHF because of their ability to reverse the neurohumoral effects of the sympathetic nervous system 13 , with ensuring symptomatic benefits by lowering heart rate (HR) and contractility, consequently lowering the mortality of CHF 2,14 . The same has been demonstrated in terms of improving survival 15–17 and quality of life (QoL) of CHF patients, indicating their importance in CHF management 1821 . On the contrary, administration of β -blockers increases the risk of depression 22 , a key factor for deteriorating QoL and increased mortality risk among CHF patients 23 .…”
Section: Introductionmentioning
confidence: 72%
“…According to the MERIT-HF 15,24 and RESOLVD studies 24 , metoprolol succinate, a cardioselective β-blocker, is one of the β-blockers recommended for preventing the incidence of death in HF patients 2 . Additionally, CHF patients reported improvement in QoL in terms of physical activity, social functions and life satisfaction compared with standard therapy 21 and placebo 25 . Previously, only one study has reported the overall effect of metoprolol on cardiac performance, motor function, and QoL in Chinese patients 26 with no separate evaluation in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…During a 3 month follow up period, the mental status was improved along with a significant improvement ( P < .001) in QoL measured by MLHFQ and SF36. [24] Our previous published study also showed an improvement in the anxiety status with metoprolol treated CHF patients. [25] In the present study, QoL showed a significant improvement with both, SF-8 and MLHFQ, from baseline to 12th month in all groups of mental status.…”
Section: Discussionmentioning
confidence: 88%
“…[21] However, limited studies have shown the effect of HF on QoL scores. [23,24,29] Management of CHF using amino-terminal pro-B type natriuretic peptide-guided therapy reported significant improvement ( P < .05) in the QoL with a lower MLHFQ score during the end of 10th month follow up. [23,29] In terms of improvement in MLHFQ scores at the end of 12th month, our study findings concurred with previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation